2017
DOI: 10.1186/s12872-017-0619-x
|View full text |Cite
|
Sign up to set email alerts
|

Silent myocarditis in systemic sclerosis detected by cardiovascular magnetic resonance using Lake Louise criteria

Abstract: BackgroundSystemic sclerosis (SSc) is an autoimmune disease characterized by microvascular abnormalities, inflammation and fibrosis. We hypothesized that myocarditis may be diagnosed in asymptomatic SSc, undergoing routine cardio-vascular magnetic resonance (CMR) for fibrosis assessment, using the Lake Louise criteria: T2 ratio, early (EGE) and late gadolinium enhanced (LGE) images.MethodsEighty-two asymptomatic SSc, diagnosed according to American College of Rheumatology criteria, aged 43 ± 5 yrs., 62 with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…A diffuse subendocardial fibrosis pattern was present in 75% of patients that died and conveyed the worse prognosis [21]. Furthermore, according to other studies, myocarditis is a common finding in SSc patients with recent-onset cardiac involvement [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…A diffuse subendocardial fibrosis pattern was present in 75% of patients that died and conveyed the worse prognosis [21]. Furthermore, according to other studies, myocarditis is a common finding in SSc patients with recent-onset cardiac involvement [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial inflammation is commonly found in early‐onset SSc. Early detection and treatment of myocardial inflammation may help to prevent myocardial fibrosis and/or further mortality …”
Section: Introductionmentioning
confidence: 99%
“…In SSc, there are some limitations of interpretation due to breathing artifacts, arrhythmia, and undistinguished diffuse myocardial inflammation from diffuse fibrosis . Mavrogeni et al reported on myocardial inflammation detection—with a prevalence of 10%—using cardiac MRI and the Lake Louise Criteria in SSc with asymptomatic cardiac involvement, and they found no correlation between myocardial inflammation and blood inflammatory indices, cardiac troponin‐T, disease characteristics, or the SSc subset. There have been no recent studies between the clinical and laboratory associations and the findings of myocardial inflammation on cardiac MRI.…”
Section: Introductionmentioning
confidence: 99%
“…As such, this demonstrates the need for a combined brain and heart MRI examination in ARD patients with cardiac symptoms, seeing as disease progression may evolve differently in the two organs. Notably, our group has previously reported that CMR findings are independent of C-reactive protein levels in ARD patients [47,51,52], often rendering biomarker-based pre-selection of patients for CMR examinations problematic. This would explain the current findings and suggests that such inflammatory biomarkers might have greater utility in evaluating brain involvement than cardiac involvement, although this needs to be corroborated by future independent studies.…”
Section: Discussionmentioning
confidence: 99%